Individual-related factors influencing the striking gender inequality in the nursing profession. A cross sectional study among nurses and student nurses from selected Hospitals and Nurses Training Institutions in the Northern Cities of Uganda. - Lalam, Lilly Grace; Nabushawo Oketcho, Florence (Student's Journal of Health Research Africa, 2022)
Background: The striking level of gender inequality (GI) in the nursing profession (NP), is partially influenced by some individual related factors. The 26.4% male, mostly suffers psychological abuse and discrimination for being academic failures but some nurses appreciates them. It’s confirmed that all nurses are academically qualified though graduate nurses are only 6% and Muslims, 3.7%. 9.1% of respondents revealed that patients/attendants mistreatment by some nurses triggered their nursing choice. The main study objectives was to established the factors influencing GI in the NP among nurses and student nurses from the selected hospital and nurses training institution in the Northern Cities of Uganda. Methodology: A cross-sectional study design was used to obtain data. Trained research assistants used a pretested structured English questionnaire to obtain raw data which were single-entered and analyzed using statistical software version 26. Frequency tables and graphs were used to describe the study variables. Univaraite and bivariate analysis methods were used to identify factors associated with GI. Variables with P-value of <0.05 with 95% confidence interval were used to declare statistical significance. Results: 383 interviewed participants generated 95.6% responses. Perpetuator of gender discrimination in the NP are mainly patients/attendants and nurses/students. 35.5% of the respondents believed that male nurses are using nursing as a stepping stone to other medical courses. Gender, education level, religious affiliation, training level, the experience of discrimination, and recommended gender for NP were the individual-related factors that were significantly associated with GI in the NP Conclusion: Gender inequality in the NP is greatly influenced by individual-related factors despite other factors. The stigmatised male nurses avoid the professional uniform to probably meet the public expectation of them being doctors. Recommendation: Swift multidisciplinary action is needed for a comprehensive and collaborative mindset change of the public about NP.